Dynamic and Static Exercises Differentially Affect Plasma Cytokine Content in Elite Endurance- and Strength-Trained Athletes and Untrained Volunteers; Frontiers in Physiology; Vol. 8 - Kapilevich L. V. Leonid Vladimirovich; Zakharova A. N. Anna; Kabachkova A. V. Anastasia; Kironenko T. A. Tatyana; Orlov S. N. Sergey Nikolaevich (2017, 2017)
Title screen